Determining Optimal Public Debt in Nepal - Prasai, Laxmi Prasad (Economic Review of Nepal, 2024)
This study examines the optimal thresholds of public debt that can facilitate economic growth in Nepal. The effect of public debt on economic growth has been estimated through the non-linear relationship between public debt and GDP growth using 47 years of yearly time series data from FY 1974/75 to 2021/22. This paper also considers the relationship between economic growth and other several controlling variables, i.e., government debt, gross capital formation, trade openness, population growth, domestic saving rate, in Nepal’s context. The ideal ratio of public debt for higher economic growth is found to be 35.44 percent of real GDP in Nepal. The tools used for time series data analysis include auto regressive distributive lag (ARDL) for long run structural modeling and error correction model for short run relationships. In the recent context of increasing volume of public debt, weakening revenue mobilization capacity of the government and volatility in GDP growth rate of Nepal, this study will be useful for the government and policy maker to adopt appropriate strategies to maintain optimal threshold of public debt for sustainable growth in Nepal. The result advocates that government should use public debt cautiously to facilitate economic growth through productive sector investments by maintaining appropriate level of public debt.